2021
DOI: 10.1002/1878-0261.13060
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into p53‐regulated cytotoxicity of combined entinostat and irinotecan against colorectal cancer cells

Abstract: Late-stage colorectal cancer (CRC) is still a clinically challenging problem. The activity of the tumor suppressor p53 is regulated via posttranslational modifications (PTMs). While the relevance of p53 Cterminal acetylation for transcriptional regulation is well-defined, it is unknown whether this PTM controls mitochondrially mediated apoptosis directly. We used wild-type p53 or p53-negative human CRC cells, cells with acetylation-defective p53, transformation assays, CRC organoids, and xenograft mouse models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Previous studies showed that class I HDAC inhibition reduced p53 levels [32,5760]. Congruently, KH16 attenuates p53 levels.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that class I HDAC inhibition reduced p53 levels [32,5760]. Congruently, KH16 attenuates p53 levels.…”
Section: Discussionmentioning
confidence: 99%
“…The increase of p21 in MV4-11 cells is not linked to an increase in p53 levels. This can be explained by sufficient levels of basal p53, and it needs to be considered that class I HDACs critically control p53 by direct lysine acetylation (Marx et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We want to emphasize the fact that the HROC-Xenobank has, already in its establishment phase, supported “standard” in vivo studies [ 46 , 47 ], detailed molecular pathway investigations [ 48 ], biomarker studies, and more basic studies which took advantage of snap-frozen samples [ 49 ]. A first pre-clinical PDX trial has been started in-house, preceded by a dose finding study [ 34 ].…”
Section: Discussionmentioning
confidence: 99%